MENYAKSIKAN MASA LALU MELALUI BIOPIC FILM DALAM KAJIAN HISTORIOGRAFI VISUAL - Sandy Allifiansyah (Bricolage : Jurnal Magister Ilmu Komunikasi, 2017)
Historical text from now on could be see in a visual form. Along with the technology, the interpretation about the past and its prominent figures become more plural. The audiences have been served the visual historiography (historiopothy) when they watched the biopic or any other historical movies. This visual historiography has a strong and weakness sides. On the positive side, we can see how the historical text is getting more fluid. There is no monopoly on the systematic historiography and single interpretation about what happened in the past. But another problem comes form on the other side about the competence and subjectivity of the historical author themselves.Keywords: discourse, narration, postmodernism, visual historiography